2020
DOI: 10.1136/jmedgenet-2019-106496
|View full text |Cite
|
Sign up to set email alerts
|

A homozygousUBA5pathogenic variant causes a fatal congenital neuropathy

Abstract: BackgroundUBA5 is the activating enzyme of UFM1 in the ufmylation post-translational modification system. Different neurological phenotypes have been associated with UBA5 pathogenic variants including epilepsy, intellectual disability, movement disorders and ataxia.Methods and resultsWe describe a large multigenerational consanguineous family presenting with a severe congenital neuropathy causing early death in infancy. Whole exome sequencing and linkage analysis identified a novel homozygous UBA5 NM_024818.3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 32 publications
0
19
1
Order By: Relevance
“…The explanation for the apparently divergent phenotype in the family reported by Cabrera-Serrano and colleagues is not currently clear. The authors showed that, compared to wild-type, the homozygous missense variant in this family (c.31C > T, p.Arg11Trp), resulted in reduced UBA5 protein abundance and a significantly reduced ability to activate UFM1 ( P < 0.05) ( Cabrera-Serrano et al 2020 ). Unlike all but one of the other UBA5 variants described to date, this variant is intronic and unlikely to be damaging in the transcript that is most highly expressed in the brain, per GTEx ( ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The explanation for the apparently divergent phenotype in the family reported by Cabrera-Serrano and colleagues is not currently clear. The authors showed that, compared to wild-type, the homozygous missense variant in this family (c.31C > T, p.Arg11Trp), resulted in reduced UBA5 protein abundance and a significantly reduced ability to activate UFM1 ( P < 0.05) ( Cabrera-Serrano et al 2020 ). Unlike all but one of the other UBA5 variants described to date, this variant is intronic and unlikely to be damaging in the transcript that is most highly expressed in the brain, per GTEx ( ).…”
Section: Discussionmentioning
confidence: 99%
“…Although 17 of 19 families reported to date with biallelic UBA5 mutations have the EIEE44 phenotype, the phenotypes of the two remaining families described by Duan et al (2016) and Cabrera-Serrano et al (2020) appear to be distinct ( Supplemental Table S1 ). Other than the fact that neither of these two families carry the p.Ala371Thr variant, there is currently no identifiable genotype–phenotype correlation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 While the UFM1 system has long been implicated in a variety of non-neurological pathological processes, 4,5 in recent years research established its involvement in neurodevelopmental disorders. [6][7][8][9][10][11][12][13][14][15] Biallelic variants in UBA5 or UFM1 have been described in cases with encephalopathy, intellectual disability, movement disorders, epilepsy, and neuropathy. Neuroimaging findings in these cases are variable and mostly consist of cerebral and cerebellar atrophy.…”
Section: Introductionmentioning
confidence: 99%